Evaluasi Penyajian Informasi dengan Aplikasi Buana Integrated Trading System (BITS) terhadap Pengendalian Stock : Studi Kasus pada PT Cahaya Buana Kemala - Iriyadi, Iriyadi; Martono, Martono (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
The purpose of this sesearch is to evaluate the presentation of information by BITS towards commodity control, especially inventory of goods at trading firm. The research conducted by the author is taken place at Cahaya Buana Kemala, Inc. in Olympic industry area, Sentul, Bogor. This company functions as distributor or supplier of furniture products. It is a national private company that often export its products as well. The outcome of the research indicates that BITS application program is able to present information needed by the management of Cahaya Buana Kemala, Inc. so that it can help controlling the available commodity stock in the field. By good serving of information, the program of BITS will be able to serve accounting to support carrying out of stock opname which constitute mounthly routine activity. Therefor, the difference between administration in BITS and administration in the field will be esier to be traced and corrected and to be found out its causes as fast as possible. Keywords: Presentation of information; Inventory control